Woven Bag Production Scheduling With Heuristic Pour Algorithm and Earliest Due Date - Afriza, Ajeng; Rochmoeljati, Rr. (Newinera Publisher, 2025)
PT. XYZ is a company engaged in manufacturing, especially in producing woven bags, which are plastic sacks made of Polypropylene (PP). PT. XYZ faces the problem of too long makespan time in the application of the First Come First Serve (FCFS) method. Although considered simple, FCFS is less efficient in complex production, especially with variations in processing time. As a result, jobs with longer processing times are often prioritized, resulting in delays in shorter jobs. This causes a longer total completion time and requires the implementation of a more efficient scheduling method to minimize makespan and improve production performance. The purpose of this study was to determine the optimal woven bag production job and to reduce makespan and delays in woven bag production with the Heuristic Pour Algorithm and Earliest due date (EDD) at PT. XYZ. From the calculation results using the first come first serve method with the job sequence 1-2-3-4-5-6, the total makespan value was 33119 or 551 hours 59 minutes. Meanwhile, the calculation using the heuristic pour algorithm method and Earliest due date (EDD) obtained the sequence of jobs 3-2-4-1-6-5 with a total makespan of 28528 minutes or 475 hours 28 minutes. The calculation using EDD also showed a decrease in lateness for each job, where the lateness of job 3 was the smallest, namely -10 days with a due date of 17 days. Based on this research, the percentage decrease in makespan value was 13.86%.